A Remembering of Culture and Community: An Exploration of the Ambiguity and Significance of Everyday Affordable Sustainable Clothing - Johnson, Leica (Auckland University of Technology, 2020)
Individuals ‘experiencing poverty often find it difficult to partake in contemporary consumption behaviours,’ consequently budget consumers are often left out of the sustainable fashion conversation. The design and making of a socially equitable clothing collection questions the inequalities related to the unaffordability of sustainable fashion and challenges the stereotypes often associated with consumers of budget clothing. Now that sportswear is a universally acceptable part of popular culture, the newly formed acceptable social boundaries associated with these types of clothes can be designed to move beyond their current understanding. Beyond the object, clothes can confirm a person’s social status (due to their known affordability) or somehow work to represent a remembering of culture and community and by doing so establish new purpose and experiences of clothes. As a response to the realities of deindustrialisation, ongoing austerity and the associated impacts of poverty in the United Kingdom, my interest lies in the space between self-expression, and at the same time, belonging. This body of work, an interchangeable affordable sustainable clothing collection, is an exploration of the ambiguity and significance of everyday affordable budget clothing and the associated negative impacts of social class positioning and stigma that can arise from this.
Keywords: Austerity; Design Futuring; Budget clothing; Streetwear; Sustainable fashion